2017
DOI: 10.4103/2277-9175.207150
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Capability of Ultra-high Temperature Milk and Ultra-high Temperature Soy Milk and their Fermented Products Determined by Four Distinct Spectrophotometric Methods

Abstract: Background:Due to the recent emerging information on the antioxidant properties of soy products, substitution of soy milk for milk in the diet has been proposed by some nutritionists. We aimed to compare four distinct antioxidant measuring methods in the evaluation of antioxidant properties of industrial ultra-high temperature (UHT) milk, UHT soy milk, and their fermented products by Lactobacillus plantarum A7.Materials and Methods:Ascorbate auto-oxidation inhibition assay, 2,2-diphenyl-1-picryl-hydrazyl-hydra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, the degraded tannins and phenolic compounds are possibly converted to antioxidative compounds [34]. On the other hand, Baghbadorani et al [35] reported that the increase in the antioxidant activity of fermented soymilk could be due to the liberation of isoflavone through the catalytic action of β-glucosidase and intracellular antioxidants of starter organisms. The increase or decrease of the antioxidant activity is dependant upon either a factor or factors in synergistic effect [5].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the degraded tannins and phenolic compounds are possibly converted to antioxidative compounds [34]. On the other hand, Baghbadorani et al [35] reported that the increase in the antioxidant activity of fermented soymilk could be due to the liberation of isoflavone through the catalytic action of β-glucosidase and intracellular antioxidants of starter organisms. The increase or decrease of the antioxidant activity is dependant upon either a factor or factors in synergistic effect [5].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous dissolved substances are found in the hydrophilic phase of milk, including those which present antioxidant activity, a property of milk which has been investigated in recent years (Baghbadorani et al, 2017;Zulueta et al, 2009;Havemose et al, 2006). Antioxidants found in or added to milk may diminish or even inhibit the oxidation of lipid compounds, which occurs as a result of exposure to light, heat, contamination by metal ions or the activity of pro-oxidative enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it helps achieve an overall uniform macroscopic homogeneous composition and properties. However, the overall efficiency of the process depends on fluid conditions and valve design (Aswathanarayan & Vittal, 2019;Azmi et al, 2019). This emerging food processing technology has been in use mainly for structuring food products, dissolution, dispersion, mixing of ingredients, encapsulation, and emulsification of blends (Pingale et al, 2023).…”
Section: High-pressure and Ultrahigh-pressure Homogenizationmentioning
confidence: 99%
“…In another study, the effect of UHPH on the bioactive compounds of soya milk has been recently studied by Toro-Funes et al ( 2014) reported that with the increase in pressure and temperature of UHPH treatment, the degree of extractability of bioactive compounds phytosterol and isoflavone was also increased, also some of the bioactive compounds did not show any rise in the values. Numerous studies (Baghbadorani et al, 2017;Xu & Chang, 2009) have been done to determine how thermal processing affects plant milk's antioxidant qualities, but more study is needed to determine how UHPH affects plant milk (Sharabi et al, 2018;Zamora & Guamis, 2015).…”
Section: Typementioning
confidence: 99%